Analisis Kemandirian Keuangan Daerah dan Potensi Pertumbuhan Kabupaten/Kota di Sulawesi Selatan Tahun 2017-2021 - Azwar Azwar (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2023)
This study aims to analyze the independence of regencies/cities in South Sulawesi Province and prospects for their economic development using a quantitative approach with share, growth, elasticity, quadrant, and Financial Capability Index (IKK) analysis methods. The results of the study show: (1) the average share value of districts/cities in South Sulawesi Province during the 2017-2021 period describes that they are not fully independent in terms of sources and allocation of regional budgets; (2) in general, the average growth rate for districts/cities in South Sulawesi Province during the 2017-2021 period show that they have good prospects and expectations for economic growth; (3) based on the quadrant mapping results, Makassar City and East Luwu Regency are in Quadrant I. In Quadrant II, there are Bantaeng, Soppeng, Gowa, Maros, Sidenreng Rappang, Enrekang, Luwu, Bulukumba, Pare-pare, Pinrang, Selayar Islands Regencies, North Toraja, Takalar, Barru, Jeneponto, and Sinjai, where almost all of them are natural resource producing areas. Furthermore, there are no districts/cities that are included in Quadrant III. In Quadrant IV, several regencies such as Bone, Palopo, Pangkajene Islands, Tana Toraja, Wajo, and North Luwu fall into this category; (4) the classification of the financial capability index resulting from the share, growth, and elasticity index values, which is equal to 0.48, is in the high category. In the pattern of regional financial capacity relations, most districts/cities in South Sulawesi Province have a consultative relationship pattern, thus the central government's interference has begun to decrease and the regions are considered capable of implementing regional autonomy.